Ответы и объяснения

2013-03-05T13:25:33+00:00

3S+6NaOH=2Na2S+Na2SO3+3H2O

S-4e=S(+4)  -1-ок-ние;в-ль

S+2e=S(-2)  -2 -в-ние;ок-ль

2S+2S=S(+4)+2S(-2)

3S=S(+4) +2S(-2)

 

Na2SO3+2HNO3=Na2SO4+2NO2+H2O

S(+4) -2e=S(+6) -1-ок-ние;в-ль

N(+5) +1e=N(+4)  -2-в-ние;ок-ль

S(+4)+2N(+5)=S(+6)+2N(+4)

 

2013-03-05T14:33:09+00:00

3S+6NaOH=2Na2S+Na2SO3+3H2O

S-4e=S(+4) -1

S+2e=S(-2) -2 

2S+2S=S(+4)+2S(-2)

3S=S(+4) +2S(-2)



Na2SO3+2HNO3=Na2SO4+2NO2+H2O

S(+4) -2e=S(+6) -1

N(+5) +1e=N(+4) -2-

S(+4)+2N(+5)=S(+6)+2N(+4)